628. Short-Term Water-Pipe (Shisha) Smoke Exposure Worsens Lung Inflammation in Mice Infected with Respiratory Syncytial Virus. (26th November 2018) - Alsuwaidi, Ahmed; AlSalam, Suhail; Varga, Steven; Nemmar, Abderrahim
Abstract: Background: Water-pipe smoking (WPS) is becoming popular all over the world and among various populations despite the growing concern about the associated deleterious health effects. Chronic cigarette smoke exposure enhances respiratory syncytial virus (RSV) pathology in mouse airways. However, the effects of exposure to WPS on the course of RSV are not known. Here, we examined the impact of short-term WPS exposure on the course of RSV in a mouse model. Methods: BALB/c mice were exposed to nose-only mainstream WPS for 30 min/day for 4 consecutive days. Control mice were exposed with the same regimen to air only. At the end of the exposure period, WPS-exposed and control mice were intranasally inoculated with RSV A2 strain. The mice were sacrificed on selected days postinfection. Several endpoints including body weight, markers of inflammation (tumor necrosis factor-α [TNF-α] and interleukin 1β [IL1β]) and oxidative stress (superoxide dismutase [SOD]), histopathology and lung viral copies were evaluated. Results: On Day 3 post-infection, mice exposed to WPS and infected with RSV exhibited significant weight loss in comparison to control mice ( P = 0.002), Figure 1. Lung infection with RSV was also associated with increased albumin in bronchoalvelar lavage fluid, a biomarker that distinguishes infection-induced lung injury from WPS-induced lung injury, Figure 2. Other biomarkers of inflammation (TNF-α and IL1β) and oxidative stress (SOD) increased in both types of injuries. In mice exposed to WPS and infected with RSV, the intensity of inflammatory infiltrates (mainly lymphocytes), the size of damage to the distal airway spaces and the size of involved area were clearly higher than in control mice. Despite the increased disease, lung viral load was not significantly affected by exposure to WPS. Conclusion: In this model, short-term water-pipe smoke exposure resulted in severe RSV disease (increased weight loss) and worsened pathology. Disclosures: All authors: No reported disclosures.